2019
DOI: 10.1007/s10775-019-09415-1
|View full text |Cite
|
Sign up to set email alerts
|

Integrating storytelling and quantitative career assessment

Abstract: Combining quantitative career assessment with narrative career counselling is a career counselling challenge. The Integrative Structured Interview (ISI) facilitates this integration through the narration of career stories based on quantitative scores, such as those of the Self-Directed Search. The aims of this single case research were to: (a) examine the process of an Integrative Structured Interview with a participant, and (b) explore it from the participant and interviewer perspectives using an interpersona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…For instance, the career assessment and dashboard function of Infinity should contribute to students' readiness as well as their self- and career-knowledge. The qualitative functions (e.g., career curriculum) facilitated the integration and alignment of diverse information instrumental to decision clarity (McMahon et al, 2020 ). The need analysis that preceded the development of Infinity (Ho and Leung, 2016 ; Leung, 2020a ) showed that tools and resources were greatly needed for career guidance in Hong Kong.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, the career assessment and dashboard function of Infinity should contribute to students' readiness as well as their self- and career-knowledge. The qualitative functions (e.g., career curriculum) facilitated the integration and alignment of diverse information instrumental to decision clarity (McMahon et al, 2020 ). The need analysis that preceded the development of Infinity (Ho and Leung, 2016 ; Leung, 2020a ) showed that tools and resources were greatly needed for career guidance in Hong Kong.…”
Section: Discussionmentioning
confidence: 99%
“…Career assessment is used as ingredients for meaning and self-identity construction. Infinity offers users with multiple tools to deepen their explorations and understanding (McMahon et al, 2020 ), and to integrate their insights from assessment and other sources of observations into life stories and action plans (see examples in Table 3 ). A CACGS with only the assessment and information components would not be able to achieve these objectives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As expected, scores increased for all career adaptability dimensions. A method for integrating storytelling and quantitative career assessment has recently been coined (McMahon et al, 2020), the ISI, which is a qualitative practical application of the story telling approach to career counseling (McMahon & Watson, 2012). It can be described as a systemic interview that provides a structured process within which clients can reflect on the meaning and relatedness of themes in their lives.…”
Section: Evidence Regarding the Effectiveness Of Narrative And Mixed ...mentioning
confidence: 99%